Three New Abietane-Type Diterpenoids from Plectranthus africanus and Their Antibacterial Activities - Nzogong, Raïssa T.; Nganou, Blaise K.; Tedonkeu, Alex T.; Awouafack, Maurice D.; Tene, Mathieu; Ito, Takuya; Tane, Pierre; Morita, Hiroyuki (Planta Medica, 2018)
Three new abietane-type diterpenoids, plectranthroyleanones A – C (1 – 3), together with five known compounds (4 – 8) were isolated from the methanol extract of the whole plant of Plectranthus africanus using column chromatography techniques. The structures of the new compounds were elucidated using a combination of 1D and 2D NMR and HRESIMS analyses. Compound 1 exhibited weak activities with minimal inhibitory concentration values of 75 µg/mL against gram-positive bacteria, Bacillus subtilis and Staphylococcus aureus, and 150 µg/mL against two gram-negative bacteria, Pseudomonas aeruginosa and Klebsiella pneumoniae, respectively, while 2 and 3 had moderate antibacterial activity against K. pneumoniae with a minimal inhibitory concentration value of 37.5 µg/mL.
Keywords: Plectranthus africanus; Lamiaceae; abietanes; plectranthroyleanone; antibacterial activity